SECURITY OF CHINA’S WARSHIP AND COAST GUARD ON ILLEGAL FISHING ACTIVITIES OF CHINA FISHERMAN IN SOUTH CHINA SEA REVIEWED FROM UNCLOS 1982 AND PRINCIPLE NON INTERVENTION - Ananda, Fauzan Rahmat (BELLI AC PACIS (Jurnal Hukum Internasional), 2021)
This research aims to determine the security of China’s warship and coast guard on illegal fishing activities of China fisherman in South China Sea reviewed from UNCLOS 1982 and principle nonintervention, with the background of various illegal fishing incidents in the South China Sea which are often protected by Chinese warships and coast guard. This research was normative legal with case approach and statute approach. The data used secondary data. The characteristic used prescriptive legal research. The techniques in the gathering of legal materials in this research was library research. This research uses deduction methods of analysis techniques, namely stemming from the rule of law and legal facts and then drawn into conclusions. From this research showed that the security of China’s warship and coast guard on illegal fishing activities of their fisherman is an act that is contrary to international law, as reviewed from UNCLOS 1982 and principle non-intervention.